Lymphocyte subsets phenotype in patients with infectious mononucleosis - Salih, Shahlaa M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Infectious mononucleosis (IM) is a lymphoproliferative disease caused primarily by the Epstein-Barr virus (EBV) infection. The initial viral infection by EBV occurs in B lymphocytes and is followed by an extensive proliferation of T lymphocytes. Previous studies on immunity to EBV (including IM) have mainly focused on activation of peripheral blood T cells, which are responsible for the lymphocytosis in blood during acute IM.Patients and Methods: Indirect immunofluorescence technique analysis was performed to detect the percentage of CD3, CD4, CD8, CD19, and CD56 positive lymphocytes.Results: Our results on the phenotype of T cells in samples from patients with infectious mononucleosis showed that there is a significant increase in percentage of CD8+ T-cells when compared with healthy group. In addition, increased in percentage of CD3 T-cells and moderately increase in CD56 (NK) cells. CD4 and CD19 percentage were significantly decrease in comparison with healthy control.Conclusion: Acute infectious mononucleosis is characterized by a marked increase in the percentage of CD3 and CD8 T- cells with a slight increase in CD56 percentage. A marked decrease in CD19 percentage and CD4/CD8 ratio was noticed.